Perjamuan Malam Sebelum Imlek: Ecclesia Domestica dan Keselamatan Kristiani - Piluit, Laurentius Fol (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2014)
Being in harmony among members of the Chinese family is of paramount importance, which can be strived for in many ways. Evening meal on the eve of Imlek is traditionaly considered as one of those very important moments. This article argues that once a year this evening meal on the eve of Imlek is the very blessed moment for the whole family to share their love to each other, to show their respect to their parents, and to offfer mutual forgiveness. At this very moment, in the new Spring season, the family earnestly expect to get many more success in the days to come. The colourful Imlek is exactly the sign for those blessings on this Spring time. The writer then tries to reflect this evening meal theologically, supposing the family as an ecclesia domestica (domestic church), and suggests some ideas for energizing family ministry, particularly among the Chinese.